The use of Ethics Decision‐Making Frameworks by Canadian Ethics Consultants: A Qualitative Study. (23rd May 2016) - Kaposy, Chris; Brunger, Fern; Maddalena, Victor; Singleton, Richard
Abstract: In this study, Canadian healthcare ethics consultants describe their use of ethics decision‐making frameworks. Our research finds that ethics consultants in Canada use multi‐purpose ethics decision‐making frameworks, as well as targeted frameworks that focus on reaching an ethical resolution to a particular healthcare issue, such as adverse event reporting, or difficult triage scenarios. Several interviewees mention the influence that the accreditation process in Canadian healthcare organizations has on the adoption and use of such frameworks. Some of the ethics consultants we interviewed also report on their reluctance to use these tools. Limited empirical work has been done previously on the use of ethics decision‐making frameworks. This study begins to fill this gap in our understanding of the work of healthcare ethics consultants.